2011
DOI: 10.1585/pfr.6.1402085
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Cross-Field Transport of Pellet Plasmoid in LHD

Abstract: A three-dimensional observation of the solid hydrogen pellet ablation has been performed by using a fast stereo imaging camera to investigate the pellet ablation dynamics. The initial velocity component of the injected pellet is maintained during ablation in a hot plasma, and the pellet penetrates to the core plasma. On the other hand, it has been observed that part of high density pellet plasmoid, which is formed around the pellet substance by ablating hydrogen pellet, intermittently breaks away from the pell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 18 publications
(19 reference statements)
1
8
0
Order By: Relevance
“…when no average effect has come into play yet. It is found that the direction given by the HPI2 code for plasmoids of small parallel length, agrees with the drift estimated from fast camera images (see Figure 12) and with the deposition profiles shifted towards the LFS plasma edge, an effect that has been reported for LFS injections in several tokamaks [5], [13,62] and in the LHD [66].…”
Section: Modelling Of Pellet Injections and Comparison With Tj-ii Expsupporting
confidence: 85%
“…when no average effect has come into play yet. It is found that the direction given by the HPI2 code for plasmoids of small parallel length, agrees with the drift estimated from fast camera images (see Figure 12) and with the deposition profiles shifted towards the LFS plasma edge, an effect that has been reported for LFS injections in several tokamaks [5], [13,62] and in the LHD [66].…”
Section: Modelling Of Pellet Injections and Comparison With Tj-ii Expsupporting
confidence: 85%
“…Such a strong acceleration inferred from equation (2) would characterize the drift during the ablation or the very early phase of homogenization, before the plasmoid expansion becomes significant. Experimentally, a breakaway plasmoid released from the ablation cloud was measured by a bifurcated fibrescope [21], and a velocity of up to 30 km s −1 was reported [31]. Although the time resolution of the experimental data, of about 5-10 µs, is insufficient to allow a comparison with theoretical predictions for the velocity on a timescale of the plasmoid detachment, the fast propagation of the deposited mass towards the direction down the magnetic field gradient is confirmed by the measurement.…”
Section: ∇B-induced Drift In the Lhdmentioning
confidence: 99%
“…Similarly to what is typically obtained in the case of LFS launched pellets in tokamaks, an outward shift of the deposited mass with respect to the ablation location was identified [20] by the Thomson scattering measurements. The propagation of the deposited mass across the magnetic field was observed spectroscopically using fast-imaging cameras [21], showing that ablatant cloudlets are expelled out of the most emissive part of the ablation cloud and then drift down the local magnetic field gradient.…”
Section: Introductionmentioning
confidence: 99%
“…It is considered that the profiles mainly changed within 1 ms from the previous results. After the pellet injection, a plasmoid component is formed 31 , 32 in the background plasma. The pellets are injected into a horizontally elongated cross-section of the plasma.…”
Section: Resultsmentioning
confidence: 99%